Rural sociology and rural development: a study of rural communities in Ethiope East local government area of Delta State, Nigeria - Okolie , Ugo Chuks; Onyema , Okwu Augustina; Bassey , Ugo Samuel (Social Sciences, Humanities and Education Journal (SHE Journal), 2023)
This study examined the influence of rural sociology on rural development in a few rural communities in Nigeria's Ethiope East Local Government Area, which is located in Delta State. In Ethiope East, Delta State, Nigeria, 400 rural residents were chosen at random from a total population of 362,753. A response rate of 71.75 percent was achieved after 287 of the 400 copies that were distributed were retrieved and examined. Data gathered were analysis through percentage, Spearman's Correlation, and linear regression using the statistical package for social sciences (SPSS) version 23. The research found a significant connection between rural sociology and rural development. The study also discovered that rural sociology has a favorable and statistically significant impact on rural development. Based on our findings, we came to the conclusion that rural sociology has a significant influence on rural development in Ethiope east local government area of Delta State, Nigeria. Thus, among other things, the study suggests that the Nigerian government employ rural sociologists to assist in putting into action successful rural policies and programs. This will encourage the growth of Nigeria's rural communities